Study of post caesarean section wound infection and microbiological epidemiology in tertiary care centre, Western Rajasthan, India - Sahay, Nehal; Jhakhar, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Surgical site infection (SSI) following C-section is a common encountered problem and needs to be analysed. In this study we have determined the incidence, risk factors and common bacterial pathogens in surgical site infection (SSI) following C-section at a tertiary care centre. Methods: A hospital based prospective study conducted for a period of 6 months. Those women whose C-section was complicated by SSI within 5 days postoperatively were included in the study. Risk factors for SSI were identified and microbiological pattern was studied. Results: Out of 62 women whose C-section was complicated by SSI within 5 days post-operatively, during this study period post caesarian SSI incidence was 0.34%. In this study post C-section SSI found as high as 43.55%, in lower socio-economic status. Among all patients, un-booked were 62.90%, Referred patients were as high as 67.74%. SSI developed in 69.35% patients without preoperative antibiotic prophylaxis. C-section done in PROM in 64.50% and as an elective emergency 79.03%, blood transfusion needed in 59.68% and type of incision being transverse (Pfannenstiel) in 88.71%. Subcutaneous suture technique used in 75.81% and secondary healing occurred in 67.74%. Most common organism grown was CoNS (coagulase negative staphylococcus) 29.03% in SSI. Conclusions: To reduce SSI, the hospital infection control system and surgical site infection surveillance program has to be established. Knowing the prevalence and risk factors will help optimal precaution and standard surgical technique to reduce SSI, which causes increased hospital stay of patients.